The role of faith in the meaning of life from the point of view of Søren Aabye Kierkegaard and Javadi Ameli - Leili Niknsfs Dehghani; Vahid Sohrabi Far; Abas Mahdavi (حکمت اسرا, 2024)
The meaning of life is considered as one of the issues that have faced serious challenges in thecontemporary world due to the change and evolution of human life today. This challenge doesnot only occur in the known life, but sometimes it also shows itself in the life based on moralityand religion, which can indicate the peak of the crisis. Signs and works can be found in thesearch for a solution to this challenge in the philosophical literature of Søren AabyeKierkegaard and the literature of Javadi Ameli. Using an explanatory-inferential analysis, thisarticle seeks the views of Soren Kier Kegard and Javadi Ameli about faith and its impact onthe meaning of human life; Because according to both philosophers, life based on faith is theonly appropriate answer and solution to deal with emptiness and meaninglessness; but thereare basic differences and similarities between Javadi Amoli's faith and Kier Kegard's faith,which will be discussed in the following text.